Altered expression of norepinephrine transporter participate in hypertension and depression through regulated TNF-α and IL-6. (17th February 2020) - Meng, Lin; Bai, Xiaoxue; Zheng, Yan; Chen, Dongmei; Zheng, Yang
ABSTRACT: Aim : We explored the role of histone modification in the association of depression-hypertension by comparing norepinephrine transporter ( NET ) gene levels in different depression-hypertensive patients. Then, we analyzed the expression of NET correlation with inflammatory cytokines to provide a new direction for detecting the association mechanism between depression and hypertension. Methods : NE expression levels in serum of diverse groups were detected by enzyme-linked immunosorbent assay. Then histone acetyltransferase (HAT), histone deacetylase (HDAC), H3K27ac, NET, TNF-α, and interleukin-6 ( IL-6 ) were detected by western blot in nine female subjects in different depression and hypertension groups, and Chromatin immunoprecipitation-polymerase chain reaction (Chip-PCR) were used to confirm the degree of acetylation affecting on the transcription level of NET gene. Meanwhile, correlation between NET with TNF/IL-6 was analyzed by SPSS19.0 software program. Finally, Quantitative real-time polymerase chain reaction (qPCR) and western blot were used to detect TNF-α and IL-6 expression levels after NET overexpression or interference treatment in human umbilical vein endothelial cells and Neuro-2a cells. Results : The expression of HAT and H3K27ac had lower levels in D-H and nonD-H group than nonD-nonH group. The results showed that higher acetylation could promote expression of NET genes. Meanwhile, the expression of NET had a significant negative correlation with IL-6 ( R = −0.933, p < 0.01) and tumor necrosis factor ( TNF ) ( R = −0.817, p < 0.01) in subjects. In addition, the results confirmed that TNF-α and IL-6 mRNA and protein partial expressions could be inhibited by NET in both HUVECs and Neuronal cells ( p < 0.01). Conclusion : In conclusion, differential expression of NET gene might function as an important factor in interaction between depression and hypertension by partially targeting TNF-α and IL-6 .